2017
DOI: 10.1186/s11671-017-1923-1
|View full text |Cite
|
Sign up to set email alerts
|

Properties of Doped GaSb Whiskers at Low Temperatures

Abstract: Temperature dependencies of GaSb whiskers’ resistance doped with Te to concentration of 1.7 × 1018 cm−3 were measured in temperature range 1.5–300 K. At 4.2 K temperature, a sharp drop in the whisker resistance was found. The observed effect is likely connected with the contribution of two processes such as the electron localization in the whiskers and transition in superconducting state at temperature below 4.2 K. The whisker magnetoconductance is considered in the framework of weak antilocalization (WAL) mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…However, we note that the p-type behavior of the underlying GaAs stem results from Ga vacancies as pointed out earlier. Another potential origin of ferromagnetism in our doped nanowires may lie in strong magnetic ordering of the 5p spins on the Te dopant atoms when the dopant concentration is near the MIT as suggested by Druzhinin, et al 17,18 and is the case in our samples. Coey 52 has recently discussed the complexity of temperature independent d 0 FM in oxides with non-magnetic cations and concluded that currently available data cannot be explained via our conventional understanding.…”
Section: Electron Energy Loss Spectroscopy Measurements(eels) Monochmentioning
confidence: 53%
See 1 more Smart Citation
“…However, we note that the p-type behavior of the underlying GaAs stem results from Ga vacancies as pointed out earlier. Another potential origin of ferromagnetism in our doped nanowires may lie in strong magnetic ordering of the 5p spins on the Te dopant atoms when the dopant concentration is near the MIT as suggested by Druzhinin, et al 17,18 and is the case in our samples. Coey 52 has recently discussed the complexity of temperature independent d 0 FM in oxides with non-magnetic cations and concluded that currently available data cannot be explained via our conventional understanding.…”
Section: Electron Energy Loss Spectroscopy Measurements(eels) Monochmentioning
confidence: 53%
“…Furthermore, the fact that ferromagnetism is observed in our doped semiconductor nanowires but not intrinsic ones suggests that it is dopant induced. We note that the doping concentration in our doped nanowires, mid-10 18 cm −3 , is in the vicinity of the metal-insulator transition (MIT) as reported by Druzhinin, et al 17,18 , which was relevant to their magnetoresistance (MR) behavior. They demonstrated that negative MR due to strong magnetic ordering occurred only when the carrier concentration of the non-magnetic Te impurities was within the MIT regime.…”
Section: Electron Energy Loss Spectroscopy Measurements(eels) Monochmentioning
confidence: 58%
“…2). There are no any oscillations of Bi2Se3 whisker magnetoresistance in contrast to behavior of magnetoresistance for InSb [12] or GaSb [11] whisker, where in wide range of impurity concentrations SdH oscillations occur. The absence of oscillations could be connected with imperfection of the whisker crystal structure or their heavily doping.…”
Section: Magnetoresistance Of Bi2se3 Whiskersmentioning
confidence: 74%
“…Our previous investigation have indicated in a possibility of coexisting Kondo effect and partial superconductivity in GaSb whiskers heavily doped to concentrations corresponding to MIT [8]. Magnetotransport properties of various heavily doped semiconductor whiskers such as Ge, InSb, GaSb at low temperatures [9][10][11][12] allowed us to establish SdH oscillations, week antilocalization as well as strong spin-orbital interaction. The current study concerns to investigation of Bi2Se3 whisker magnetoresistance in low temperature range (1.5-77 K) and high magnetic field up to 10 T. Low temperature superconductivity with critical temperature Tc near 5.3 K as well as anomalous magnetoresistance upturn is revealed in the whiskers and likely connected with 2D states of the whisker surface.…”
Section: Introductionmentioning
confidence: 88%
“…1, curves 2, 3). Sharp drops of GaSb whiskers resistance at temperatures below 1.7 and 4.2 K are likely correspond to partial superconductivity of the whiskers and was described elsewhere [16].…”
Section: Temperature Dependences Of Gasb Whisker Resistancementioning
confidence: 99%